Análise da expressão gênica e conteúdo proteico de ABCB10, APEX1 e HMGB1 em pacientes com beta talassemia maior e intermediaria - Silva, João Pedro Maia de Oliveira da (Universidade Federal de São Carlos, 2017)
Beta thalassemias (BT) are a group of hereditary diseases characterized by the partial or total suppression of beta globin chains synthesis. Clinically, it manifests itself in three distinct forms: minor (BTm), intermedia (BTI) and major (BTM), and are differentiated by the frequency of transfusions, being the most severe form BTM. Since it is known in the literature that BT phenotype occurs independently of the genotype, a study conducted by the group, evaluated globally, genes that were differentially expressed in patients who had the same genotype, but different clinical presentation. By analyzing these results and looking for genes related to the increase of reactive oxygen species (ROS), responsible for causing cell damage and collaborating even more with the reduction of the erythrocyte lifespan observed in these patients, we identified the genes ABCB10, APEX1 and HMBG1 as differentially expressed, the former being increased in BTI patients and the latter two being increased in BTM. Peripheral blood samples extracted from a control group (n = 9), a BTI group (n = 8) and a BTM group (n = 4) were used to perform the real-time PCR experiments; for the experiments with CD34 + cells two healthy cultures and two containing the IVSI-6 mutation were used on the 7th, 10th and 13th days; A control group (n = 4), a BTI group (n = 5) and a BTM group (n = 6) were used to determine the protein content of APEX1, and a control group (n = 4) ) and a BTI group (n = 5) for the HMGB1 experiment. The data were analyzed using the GraphPad Prism 6 software and considered significant values of p <0.005. Using the real-time PCR technique (qPCR), we confirmed these results in a larger number of patients. The ABCB10 gene, on average, was 5 times more expressed in BTI patients (p = 0.0077). The APEX1 and HMGB1 genes were differentially expressed in patient BTM (both 3 times). Analyzing the expression of these genes during differentiation of thalassemic beta cells in CD34 + cell culture, compared to healthy cells, by real-time PCR, we found an increase in ABCB10 expression and a decrease in APEX1 and HMGB1 at the end of the differentiation. A protein analysis using western blot indicated that the protein content of APEX1 is increased in the two phenotypes of BT indicating its relation to the disease independent of the phenotype. Since erythroid cells did not show detectable amounts of HMGB1 in the cytoplasm, it was analyzed in the plasma of healthy individuals and BTI, showing a significant increase of this protein in patients. In this way, we conclude that our results contribute with unpublished data for the literature and can show in the case of differential expression of ABCB10, a more efficient response against oxidative stress, besides an important role in the erythroid differentiation in BTI patients. The higher production of APEX1 in beta-thalassemic patients seems to be independent of the phenotype being associated with the disease and related to the increase of oxidative stress observed in these patients. Finally, increased secretion of HMGB1 in the plasma of patients may be associated with prolonged inflammatory conditions, contributing to systemic cytotoxicity. The data presented here contribute to a better understanding of the disease, pointing out new targets for future studies.
Analysis of gene expression and protein content of ABCB10, APEX1 and HMGB1 in patients with beta thalassemia major and intermediaria
Keywords: Beta talassemia; Anemia hemolítica; APEX1; HMGB1; ABCB10; Expressão gênica; Estresse oxidativo; Estrés oxidativo; Expresión génica; Oxidative stress; Gene expression; Hemolytic anemia; Beta thalassemia; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA HUMANA E MEDICA